Potential use of cowpea protein hydrolysate as a dietary supplement in broiler chickens: effects on growth, intestinal morphology, muscle lipid profile, and immune status - Samar A. Tolba; Shimaa A. Amer; Ahmed Gouda; Ali Osman; Wafaa R. I. A. Sherief; Amany I. Ahmed; Ghada I. Abd El-Rahman; Abdel-Wahab A. Abdel-Warith; Elsayed M. Younis; Simon J. Davies; Elshimaa M. Roushdy (Italian Journal of Animal Science)
In the current study, we tested the effects of dietary cowpea protein hydrolysate (CPH) on broilers’ growth, carcase traits, intestinal histomorphology, The fatty acid profile of breast muscle, blood biochemical parameters, and immune status. Three-day age male Ross-308 broilers (n = 300, average weight 86.72 g ± 0.20) were distributed into five groups and fed on five diets supplied with five levels of CPH at 0, 2, 4, 6, and 8 g kg−1 for 35 days. The results revealed that dietary CPH did not change (P < 0.05) the broilers’ growth performance or carcase traits, except for a quadratic decrease (P < 0.05) in FCR at concentrations 2 and 4 g kg−1 during the finisher period. The villus heights (VH) and goblet cell count (GCC) were increased (P < 0.05) in the duodenum and jejunum; however, the villus width decreased (P < 0.05) in the duodenum without showing changes (P < 0.05) in the jejunum and ileum. Dietary supplementation with 6 g CPH kg−1 increased (P < 0.05) the duodenal crypt depth (CD). Dietary supplementation with 8 g CPH kg −1 increased the VH: CD in the duodenum compared to the control; nevertheless, a quadratic (P < 0.05) change was reported in the jejunum. The VH: CD did not change (P < 0.05) in the ileum; however, dietary supplementation with 6 CPH kg−1 increased (P < 0.05) the ileal VH and GCC. The inclusion of CPH led to a linear (P < 0.05) increase in the total n-3 polyunsaturated fatty acids (PUFA), n-6 PUFA, and n-3/n-6 PUFA in broilers’ breast muscle. An increase in the assessed metabolic and immune status indices was reported, as evidenced by increases (P < 0.05) in thyroid hormones, growth hormone, total protein, albumin, globulin, lysozymes, interferon-gamma, interleukin10, and complement 3 serum levels. However, the serum glucose and leptin levels did not show significant (p > 0.05) changes in response to dietary CPH. Moreover, the dietary CPH levels 4–8 g kg−1 upregulated the immunostaining of IgG in the spleen of these groups. These findings suggested that including CPH in broiler diets could be an effective candidate for modulating the chickens’ metabolic and immune status; however, it had no increased effect on broiler growth.